Polymers for energy storage and conversion - Mittal, Vikas (Polymer science and plastics engineering., 2013)
Polymers are increasingly finding applications in the areas of energy storage and conversion. A number of recent advances in the polymer molecular structure control thereby tuning of the polymer properties have led to these applications. This book assimilates these advances in the form of a comprehensive text which includes the synthesis and properties of a large number of polymer systems for applications in the areas of lithium batteries, photovoltaics, solar cells, etc. Polymers for Energy Storage and Conversion describes: PVAc-based polymer blend electrolytes for.